Irreversible investment in oligopoly - Jan-Henrik Steg (Bielefeld University, Institute of Mathematical Economics (IMW), 2009)
We offer a new perspective on games of irreversible investment under uncertainty in continuous time. The basis is a particular approach to solve the involved stochastic optimal control problems which allows to establish existence and uniqueness of an oligopolistic open loop equilibrium in a very general framework without reliance on any Markovian property. It simultaneously induces quite natural economic interpretation and predictions by its characterization of optimal strategies through first order conditions. The construction of equilibrium policies is then enabled by a stochastic representation theorem. A stepwise specification of the general model leads to further economic conclusions. We obtain explicit solutions for Lévy processes.
urn:nbn:de:hbz:361-14605
Keywords: C73; D43; D92; 330; Irreversible investment; Stochastic game; Oligopoly; Real options; Equilibrium; Irreversibility of Investment; Stochastisches Spiel; Realoption; Kontrolltheorie; Oligopol; Theorie